Penerapan PBL dalam Meningkatkan Aktivitas Siswa pada Pembelajaran PAI di UPT SDN 03 Pancung Tebal - Nurkhalis, Nurkhalis (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to determine the impact of applying the Project-Based Learning (PBL) model on student learning outcomes in the topic of the Story of the Hijrah of Prophet Muhammad SAW to Madinah in class IV at SD Negeri 03 Pancung Tebal. The research was conducted in two cycles, with each cycle involving the observation of student and teacher activities as well as evaluation of learning outcomes. The results show that the application of the PBL model in Cycle II showed significant improvement compared to Cycle I. In Cycle II, 90% of students achieved the Minimum Mastery Criteria (MMC) and student activity increased with a 92% participation rate in the very active category. Teachers also showed improvement in classroom management. Based on these findings, it can be concluded that the PBL model is effective in enhancing student learning outcomes, as well as their activity and collaborative skills in Islamic Religious Education learning.